2022
DOI: 10.3390/foods11081141
|View full text |Cite
|
Sign up to set email alerts
|

Property of Phytosterols and Development of Its Containing Mayonnaise-Type Dressing

Abstract: Phytosterols are functional ingredients with known efficacy and safety. Phytosterols are found as free sterols or as their esters with fatty acids. Although phytosterol esters are soluble in oil and have been used in many commercial foods, it has been difficult to similarly use free phytosterols since they are insoluble in water and practically insoluble in oil. We have developed mayonnaise-type dressing materials using free phytosterols since people who are conscious about cholesterol intake are likely to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…It is known that some responders are prone to increased serum cholesterol concentrations when cholesterol is ingested [ 42 , 43 ]. Furthermore, dietary influences such as functional components that reduce cholesterol absorption, such as phytosterols, soy protein, or dietary fiber, should be considered [ 44 , 45 , 46 , 47 , 48 ]. Chicken eggs’ functional components, specifically egg yolk phospholipids, have been reported to suppress cholesterol absorption [ 49 ].…”
Section: Egg White Protein Improves Lipid Metabolismmentioning
confidence: 99%
“…It is known that some responders are prone to increased serum cholesterol concentrations when cholesterol is ingested [ 42 , 43 ]. Furthermore, dietary influences such as functional components that reduce cholesterol absorption, such as phytosterols, soy protein, or dietary fiber, should be considered [ 44 , 45 , 46 , 47 , 48 ]. Chicken eggs’ functional components, specifically egg yolk phospholipids, have been reported to suppress cholesterol absorption [ 49 ].…”
Section: Egg White Protein Improves Lipid Metabolismmentioning
confidence: 99%
“…Plant sterols/ Phytosterols: Phytosterols are naturally occurring chemicals found in vegetable oils and nuts [16]. It is commercially added to margarine, mayonnaise, yogurt, cheese and some sauces [17,18].…”
Section: Dietary Fatty Acidsmentioning
confidence: 99%
“…In this review article an initiative has been made to refer the preparation of Nutella from yam bean milk that provides a lactose-free alternative for individuals with lactose intolerance and others who need to avoid whole milk due to specific health conditions such as hypothyroidism, polycystic ovarian diseases, celiac disease, and gastritis (Katan M. B et al, 2003), ( Jayaraman et al, 2021) Health benefits of phytosterol: Phytosterols have a long history of safe usage and are recognized for their effectiveness in reducing cholesterol levels. They have been employed for this purpose for a significant period and have also been linked to anti-inflammatory, antioxidant, and other positive effects (Matsuoka R., 2022). While some studies have indicated that phytosterols may have an impact on the reproductive system, primarily through their influence on estrogenic activity, it's important to note that no adverse reactions have been reported in healthy individuals.…”
mentioning
confidence: 99%